Nutrient-rich elegance: A comprehensive evaluation of garden and cut rose cultivars for culinary and nutritional significance - Firoozeh Pourzarnegar; Davood Hashemabadi; Mohammad Sadegh Allahyari (Ornamental Horticulture, 2025)
Edible flowers have introduced a new dimension to healthy living. The rose can serve as a valuable food source. This research investigates the influence of properties included antioxidant capacity (AC), nutritional value (NV), biological value (BV), macro and micro-nutrients, pigments, organoleptic and consumer preferences properties on the selection of green space and cut rose cultivars, specifically ‘Rainbows End,’ ‘Crimson Siluetta,’ ‘Hella,’ ‘Avalanche,’ ‘Dolce Vita,’ and ‘Samurai.’ The selection criteria were weighed up using the Criteria Importance Through the Inter-Criteria Correlation (CRITIC) method, based on experts’ point of view. Multi-criteria decision-making techniques, such as Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), Additive Ratio Assessment (ARAS) and Weighted Aggregates Sum Product Assessment (WASPAS) were subsequently applied for ranking rose cultivars. Among the rose cultivars studied, the ‘Hella’ cultivar exhibited the highest biological value and pigment content, while the ‘Crimson Siluetta’ cultivar demonstrated the highest concentrations of macro and microelements, as well as the greatest antioxidant capacity. The ‘Rainbows End’ cultivar was found to have the highest nutritional value and superior organoleptic properties. Among the cut branch cultivars, the ‘Samurai’ cultivar, alongside the ‘Crimson Siluetta’, showed the highest levels of macro- and microelements. The findings indicated that all examined cultivars are rich in nutritious compounds suitable for human consumption. Notably, the ‘Hella’ cultivar emerged as the top choice, while ‘Rainbows End’ was ranked as the least preferred for inclusion in daily diets.